Penentuan Strategi Pembinaan UMKM Provinsi DKI Jakarta Dengan Menggunakan Metode AHP TOPSIS - Dino Caesaron (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2014)
This study examines polices which will be used as strategy development UMKM of DKI Jakarta Provincial. The method used is Analytical Hierarchy Process (AHP) adn Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). AHP used to restucture AHP used to restructure problems decision be shape of hierarchy and calculate weight from each faktors, while TOPSIS used to calculate rank from alternatif solution on AHP, that is with chooses the best alternatif solution based on nearest distance from ideal solution.Based on calculation of data used AHP methods, demographics/population get the highest weight = 0.413. Meanwhile, the calculation of TOPSIS showed capital policy with number of value = 0.929 is better alternatif solution than ideal solution.Based on that two methods, the result is identifying that the capital policy is the best strategy to applied in develop policy of micro business, small and medium.